Lamwntig cities in Andalusian poetry - خضر , رامي عبد الكريم; فارس , عيسى; قداح , رؤى (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The tragedy of the fall of Andalusia is one of the most severe tragedies that occurred in Arab history. It represents the destructions of prosperous human civilization and Islamic landmarks that left their mark on history. This tragedy expanded until it touched the land, thought, conscience and mind that spread the light of civilization in the Andalusian peninsula. That land whose love for its land was mixed with the souls of its people , and its shadows , rivers and trees mixed with their souls and hearts. The tragedy of the fall of Andalusia turned the lights of Andalusia into complete darkness and turned its overflowing palaces and inhabited cities into ruins. This tragedy has also left its marks on the Arab conscience. The poets traced this tragedy , chronicling the misfortunes and calamities that happened in Andalusia , immortalizing the Andalusian feeling of sadness and despair over what happened to their homeland. Expressing these feelings with tears and crying in poetic, lamentable scenes that reflect sincere feelings that are less than their counterparts in Arabic poetry.